Peripheral Blood Mitochondrial DNA Copy Number Obtained From Genome-Wide Genotype Data Is Associated With Neurocognitive Impairment in Persons With Chronic HIV Infection. (1st April 2019) - Hulgan, Todd; Kallianpur, Asha R.; Guo, Yan; Barnholtz-Sloan, Jill S.; Gittleman, Haley; Brown, Todd T.; Ellis, Ronald; Letendre, Scott; Heaton, Robert K.; Samuels, David C.
Abstract : Background: Mitochondrial DNA (mtDNA) copy number varies by cell type and energy demands. Blood mtDNA copy number has been associated with neurocognitive function in persons without HIV. Low mtDNA copy number may indicate disordered mtDNA replication; high copy number may reflect a response to mitochondrial dysfunction. We hypothesized that blood mtDNA copy number estimated from genome-wide genotyping data is related to neurocognitive impairment (NCI) in persons with HIV. Methods: In the CNS HIV Antiretroviral Therapy Effects Research (CHARTER) study, peripheral blood mtDNA copy number was obtained from genome-wide genotyping data as a ratio of mtDNA single-nucleotide polymorphism probe intensities relative to nuclear DNA single-nucleotide polymorphisms. In a multivariable regression model, associations between mtDNA copy number and demographics, blood cell counts, and HIV disease and treatment characteristics were tested. Associations of mtDNA copy number with the global deficit score (GDS), GDS-defined NCI (GDS ≥ 0.5), and HIV-associated neurocognitive disorder (HAND) diagnosis were tested by logistic regression, adjusting for potential confounders. Results: Among 1010 CHARTER participants, lower mtDNA copy number was associated with longer antiretroviral therapy duration ( P < 0.001), but not with d-drug exposure ( P = 0.85). mtDNA copy number was also associated with GDS ( P = 0.007), GDS-defined NCI ( P < 0.001), and HAND ( P = 0.002). In all analyses, higher mtDNA copy number was associated with poorer cognitive performance. Conclusions: Higher mtDNA copy number estimated from peripheral blood genotyping was associated with worse neurocognitive performance in adults with HIV. These results suggest a connection between peripheral blood mtDNA and NCI, and may represent increased mtDNA replication in response to mitochondrial dysfunction. Abstract : Supplemental Digital Content is Available in the Text.